Education on Early Detection of Knee Pain At Dungus Madiun Regional Hospital - Putu Mariska Abdi Cahyani; Kristiyono Putro; Anita Faradilla Rahim (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Dungus Regional General Hospital is one of the public hospitals in the city of Madiun. Many patients who visit hospitals, especially physiotherapy clinics, are elderly people who are experiencing degenerative processes. The degenerative process is a decrease in physical function, one of which is musculoskeletal, such as knee pain. There are still many elderly people who do not know the signs and symptoms of knee pain and the right time for treatment. Based on this, education was carried out regarding early detection of pain in the knee. Counseling was presented using PowerPoint media, holding a question-and-answer session, and educating the elderly to seek treatment immediately if they experienced knee pain. The education process is going well, people are starting to understand the signs and symptoms of knee pain. By providing outreach to the public, it is hoped that it can increase the expansion of public knowledge about the signs and symptoms of knee pain, risk factors and early detection of knee pain.